Power Sharing Stakeholder of Child-Friendly City Task Force - Nila Wahyuni; Maryam Jamilah; Hidayatul Fajri (Universitas Teuku Umar, 2022)
The task force collaboration forum is present to strengthen and increase stakeholders' commitment to developing Child-Friendly Cities in Padang City. However, the optimization of this forum has not been appropriately achieved. Previous research has shown that the cause of this is sectoral ego, low stakeholders understanding, a master plan suitable for children has not been formed. At the same time, the involvement and linkage of stakeholders in the task force is a determining factor for the success of a collaboration. Furthermore, a power balance must be established between stakeholders during deliberation and decision-making. This study aimed to analyze power-sharing in the collaborative forum of Padang City Child-Friendly Task Force. The analytical method used is stakeholder mapping and social networks analysis. Stakeholders involved in the Padang City child-friendly task force have diverse interests and influences. Eighteen parties consist of two actors as key players, two as subject, seven as context center, and seven as the crowd. The interaction pattern of the stakeholders in the form of information flow is not evenly distributed. Several participants can bridge the disconnection of this information network on the condition that the strong participants must establish a relationship with the weak. A more decentralized structure and precise working mechanism are needed to control the power imbalance among stakeholders